NATO's Mediterranean initiative : policy issues and dilemmas - Larrabee, F. Stephen (Rand, 1998)
Since 1989, NATO has concentrated most of its energy on enlargement to Eastern Europe and internal adaptation; the Mediterranean has received only sporadic attention. However, in the coming decades, the Mediterranean region is likely to become more important--real security problems may be on the Alliance's Southern periphery--in the Balkans, the Mediterranean, and the Caucasus. In addition, the expansion of the Barcelona process will force NATO to play a more active role in the Mediterranean. As the European Union (EU) becomes more deeply involved in the Mediterranean region, Mediterranean issues will increasingly become part of the European security agenda--and invariably part of NATO's agenda as well. This will make close coordination between the EU and NATO in the Mediterranean more necessary and require the two organizations to work out a more explicit division of labor. The increasing importance of such issues as drug trafficking, terrorism, and the proliferation of weapons of mass destruction will also thrust Mediterranean issues more forcefully onto the NATO agenda. This report discusses these issues in the context of past and present Mediterranean initiatives; in the context of dialogues with such non-NATO member countries as Egypt, Israel, Jordan, Mauritania, Morocco, and Tunisia; and with a view toward what the nature and content of the NATO policy regarding the Mediterranean should be and how it can be most effectively implemented.